Involvement of two uptake mechanisms of gold and iron oxide nanoparticles in a co-exposure scenario using mouse macrophages - Vanhecke, Dimitri; Kuhn, Dagmar A.; Jimenez de Aberasturi, Dorleta; Balog, Sandor; Milosevic, Ana; Urban, Dominic; Peckys, Diana; de Jonge, Niels; Parak, Wolfgang J.; Petri-Fink, Alke; Rothen-Rutishauser, Barbara (Beilstein Journal of Nanotechnology, 2017)
Little is known about the simultaneous uptake of different engineered nanoparticle types, as it can be expected in our daily life. In order to test such co-exposure effects, murine macrophages (J774A.1 cell line) were incubated with gold (AuNPs) and iron oxide nanoparticles (FeOxNPs) either alone or combined. Environmental scanning electron microscopy revealed that single NPs of both types bound within minutes on the cell surface but with a distinctive difference between FeOxNPs and AuNPs. Uptake analysis studies based on laser scanning microscopy, transmission electron microscopy, and inductively coupled plasma optical emission spectrometry revealed intracellular appearance of both NP types in all exposure scenarios and a time-dependent increase. This increase was higher for both AuNPs and FeOxNPs during co-exposure. Cells treated with endocytotic inhibitors recovered after co-exposure, which additionally hinted that two uptake mechanisms are involved. Cross-talk between uptake pathways is relevant for toxicological studies: Co-exposure acts as an uptake accelerant. If the goal is to maximize the cellular uptake, e.g., for the delivery of pharmaceutical agents, this can be beneficial. However, co-exposure should also be taken into account in the case of risk assessment of occupational settings. The demonstration of co-exposure-invoked pathway interactions reveals that synergetic nanoparticle effects, either positive or negative, must be considered for nanotechnology and nanomedicine in particular to develop to its full potential.
Keywords: co-exposure; endocytosis; live cell imaging; nanoparticles; quantitative microscopy

(untitled) - Gwinn, M. R.; Vallyathan, V. (Environ. Health Perspect., 2006)

(untitled) - Mazzola, L. (Nat. Biotechnol., 2003)

(untitled) - Baetke, S. C.; Lammers, T.; Kiessling, F. (Br. J. Radiol., 2015)

(untitled) - Iversen, T.-G.; Skotland, T.; Sandvig, K. (Nano Today, 2011)

(untitled) - Nazarenus, M.; Zhang, Q.; Soliman, M. G.; Del Pino, P.; Pelaz, B.; Carregal-Romero, S.; Rejman, J.; Rothen-Rutishauser, B.; Clift, M. J. D.; Zellner, R.; Nienhaus, G. U.; Delehanty, J. B.; et al. (Beilstein J. Nanotechnol., 2014)

(untitled) - Rivera-Gil, P.; Jimenez de Aberasturi, D.; Wulf, V.; Pelaz, B.; Del Pino, P.; Zhao, Y.; De la Fuente, J. M.; Ruiz de Larramendi, I.; Rojo, T.; Liang, X.-J.; Parak, W. J. (Acc. Chem. Res., 2013)

(untitled) - Kumari, S.; Mg, S.; Mayor, S. (Cell Res., 2010)

(untitled) - Conner, S. D.; Schmid, S. L. (Nature, 2003)

(untitled) - Mahmoudi, M.; Saeedi-Eslami, S. N.; Shokrgozar, M. A.; Azadmanesh, K.; Hassanlou, M.; Kalhor, H. R.; Burtea, C.; Rothen-Rutishauser, B.; Laurent, S.; Sheibanih, S.; Valih, H. (Nanoscale, 2012)

(untitled) - Unfried, K.; Albrecht, C.; Klotz, L.-O.; Von Mikecz, A.; Grether-Beck, S.; Schins, R. P. F. (Nanotoxicology, 2007)

(untitled) - Fröhlich, E. (Int. J. Nanomed., 2012)

(untitled) - Hühn, D.; Kantner, K.; Geidel, C.; Brandholt, S.; De Cock, I.; Soenen, S. J. H.; Rivera-Gil, P.; Montenegro, J.-M.; Braeckmans, K.; Müllen, K.; Nienhaus, G. U.; Klapper, M.; et al. (ACS Nano, 2013)

(untitled) - Rejman, J.; Oberle, V.; Zuhorn, I. S.; Hoekstra, D. (Biochem. J., 2004)

(untitled) - Huang, M.; Ma, Z.; Khor, E.; Lim, L.-Y. (Pharm. Res., 2002)

(untitled) - Brandenberger, C.; Mühlfeld, C.; Ali, Z.; Lenz, A. G.; Schmid, O.; Parak, W. J.; Gehr, P.; Rothen-Rutishauser, B. (Small, 2010)

(untitled) - Tedja, R.; Lim, M.; Amal, R.; Marquis, C. (ACS Nano, 2012)

(untitled) - Freese, C.; Unger, R. E.; Deller, R. C.; Gibson, M. L.; Brochhausen, C.; Klok, H.-A.; Kirkpatrick, C. J. (Biomater. Sci., 2013)

(untitled) - Kasper, J.; Hermanns, M. I.; Bantz, C.; Utech, S.; Koshkina, O.; Maskos, M.; Brochhausen, C.; Pohl, C.; Fuchs, S.; Unger, R. E.; Kirkpatrick, C. J. (Eur. J. Pharm. Biopharm., 2013)

(untitled) - Li, W.; Liu, R.; Wang, Y.; Zhao, Y.; Gao, X. (Small, 2013)

(untitled) - Peckys, D. B.; De Jonge, N. (Nano Lett., 2011)

(untitled) - Peckys, D. B.; De Jonge, N. (Microsc. Microanal., 2014)

(untitled) - Geiser, M.; Rothen-Rutishauser, B.; Kapp, N.; Schurch, S.; Kreyling, W.; Schulz, H.; Semmler, M.; Im Hof, V.; Heyder, J.; Gehr, P. (Environ. Health Perspect., 2005)

(untitled) - Rothen-Rutishauser, B. M.; Schürch, S.; Haenni, B.; Kapp, N.; Gehr, P. (Environ. Sci. Technol., 2006)

(untitled) - Rimai, D. S.; Quesnel, D. J.; Busnaia, A. A. (Colloids Surf., A, 2000)

(untitled) - Guo, B.; Zebda, R.; Drake, S. J.; Sayes, C. M. (Part. Fibre Toxicol., 2009)

(untitled) - Hühn, J.; Carrillo-Carrion, C.; Soliman, M. G.; Pfeiffer, C.; Valdeperez, D.; Masood, A.; Chakraborty, I.; Zhu, L.; Gallego, M.; Yue, Z.; Carril, M.; Feliu, N.; et al. (Chem. Mater., 2017)

(untitled) - Hinderliter, P. M.; Minard, K. R.; Orr, G.; Chrisler, W. B.; Thrall, B. D.; Pounds, J. G.; Teeguarden, J. G. (Part. Fibre Toxicol., 2010)

(untitled) - Rodriguez-Lorenzo, L.; Rothen-Rutishauser, B.; Petri-Fink, A.; Balog, S. (Part. Part. Syst. Charact., 2015)

(untitled) - Kim, J. A.; Åberg, C.; Salvati, A.; Dawson, K. A. (Nat. Nanotechnol., 2012)

(untitled) - Chithrani, B. D.; Ghazani, A. A.; Chan, W. C. W. (Nano Lett., 2006)

(untitled) - Lehmann, A. D.; Parak, W. J.; Zhang, F.; Ali, Z.; Röcker, C.; Nienhaus, G. U.; Gehr, P.; Rothen-Rutishauser, B. (Small, 2010)

(untitled) - Zajif, H. S.; Zyuzin, M. V.; Hussain, I.; Parak, W. J.; Carregal-Romero, S. (RSC Adv., 2016)

(untitled) - Rothen-Rutishauser, B.; Kuhn, D. A.; Ali, Z.; Gasser, M.; Amin, F.; Parak, W. J.; Vanhecke, D.; Fink, A.; Gehr, P.; Brandenberger, C. (Nanomedicine, 2013)

(untitled) - Kuhn, D. A.; Vanhecke, D.; Michen, B.; Blank, F.; Gehr, P.; Petri-Fink, A.; Rothen-Rutishauser, B. (Beilstein J. Nanotechnol., 2014)

(untitled) - Pelkmans, L.; Kartenbeck, J.; Helenius, A. (Nat. Cell Biol., 2001)

(untitled) - Hayer, A.; Stoeber, M.; Ritz, D.; Engel, S.; Meyer, H. H.; Helenius, A. (J. Cell Biol., 2010)

(untitled) - Mundy, D. I.; Li, W. P.; Luby-Phelps, K.; Anderson, R. G. (Mol. Biol. Cell, 2012)

(untitled) - Kohler, F.; Rohrbach, A. (Biophys. J., 2015)

(untitled) - Heusermann, W.; Hean, J.; Trojer, D.; Steib, E.; Von Bueren, S.; Graff-Meyer, A.; Genoud, C.; Martin, K.; Pizzato, N.; Voshol, J.; Morrissey, D. V.; Andaloussi, S. E.; et al. (J. Cell Biol., 2016)

(untitled) - Lehmann, M. J.; Sherer, N. M.; Marks, C. B.; Pypaert, M.; Mothes, W. (J. Cell Biol., 2005)

(untitled) - Meyer, R. K.; Aebi, U. (J. Cell Biol., 1990)

(untitled) - Deng, R.; Lin, D.; Zhu, L.; Majumdar, S.; White, J. C.; Gardea-Torresday, J. L.; Xing, B. (Nanotoxicology, 2017)

(untitled) - Hyeon, T.; Lee, S. S.; Park, J.; Chung, Y.; Na, H. B. (J. Am. Chem. Soc., 2001)

(untitled) - Brust, M.; Walker, M.; Bethell, D.; Schiffrin, D. J.; Whyman, R. (J. Chem. Soc., Chem. Commun., 1994)

(untitled) - Bogner, A.; Thollet, G.; Basset, D.; Jouneau, P.-H.; Gauthier, C. (Ultramicroscopy, 2005)

(untitled) - Peckys, D. B.; Baudoin, J.-P.; Eder, M.; Werner, U.; De Jonge, N. (Sci. Rep., 2013)

(untitled) - Ring, E. A.; Peckys, D. B.; Dukes, M. J.; Baudoin, J. P.; De Jonge, N. (J. Microsc., 2011)

(untitled) - Hermannsdorfer, J.; Tinnemann, V.; Peckys, D. B.; De Jonge, N. (Microsc. Microanal., 2016)

R: A language and environment for statistical computing - R Core Team (R Foundation for Statistical Computing, 2014)
http://www.R-project.org/